Una investigación sobre los esquemas conceptuales del continuo. Ensayo de un cuestionario
In order to survey how students conceive the idea of continuum as they begin their training on Calculus, we have established a questionnaire and an analytical approach to responses, fully rooted in networks. The theoretical framework is based on the Dreyfus and Vinner idea of «concept image», where we attune the expression «perception of a property». We have tested the questionnaire on 74 students in the range of 16-17 years old, acquiring valuable information in return about their perception on non-discrete ordering. On the other hand, we have established a draft ordered system for models